Topological, nonreciprocal, and multiresonant slow light beyond the time-bandwidth limit - Kosmas L. Tsakmakidis; Konstantinos Baskourelos; Tomasz Stefański (Appl. Phys. Lett., 2021)
Topologically protected transport has recently emerged as an effective means to address a recurring problem hampering the field of slow light for the past two decades: its keen sensitivity to disorders and structural imperfections. With it, there has been renewed interest in efforts to overcome the delay-time-bandwidth limitation usually characterizing slow-light devices, on occasion thought to be a fundamental limit. What exactly is this limit, and what does it imply? Can it be overcome? If yes, how could topological slow light help, and in what systems? What applications might be expected by overcoming the limit? Our Perspective here attempts addressing these and other related questions while pointing to important new functionalities both for classical and quantum devices that overcoming the limit can enable.